The Relationship Between Social Support and Work Stress in Nurses at Bhayangkara Hospital, Gorontalo - Nikmah Elsah Rustam; Salahuddin Liputo; Sri Ayu M Kurniawati (Journal of Community Health Provision, 2026)
This study aims to determine the relationship between social support and work stress among nurses at Bhayangkara Hospital, Gorontalo. This research uses a uatitative research design with a population of 80 nurses. The total sample was 80 nurses using the technique total sampling. The research result showed that the work stress level of nurses was in the medium category for 61nurses with a percentage of 76,3%. The social support of nurses is in the medium category as many as 61 nurses with a percentage of 76,3%. Based on the results of the correlation test rank spearmen with correlation value (r) of – 0.592 and a sig value (p) = 0,000 (p<0.05). so it can be concluded that there is a significant negative relationship between social support and work stress in nurses at Bhayangkara Hospital, Gorontalo. This Shows that the higher the social support, the lower the work stres for nurses.